GENETIC DIFFERENTIATION AMONG POPULATIONS OF Chromobotia macracanthus BLEEKER FROM SUMATRA AND KALIMANTAN BASED ON SEQUENCING GENE OF MTDNA CYTOCHROME B AND NUCLEUS DNA RAG2 - Sudarto Sudarto; Kafi Hidonis; Emmanuel Paradis (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2008)
Research on genetic differentiation among populations of Chromobotia macracanthus Bleeker from Sumatra, based on sequencing gene of mtDNA Cytochrome b and nucleus DNA RAG2 has been done. The objectives of the study were to obtain the representation of genetic differentiation among population of clown loach fishes or botia (Chromobotia macracanthus) from Sumatra and Kalimantan and to estimate the time divergence of both population group of botia. Samples of botia population were taken from 3 rivers in Sumatra namely Batanghari, Musi, and Tulang Bawang and one river from Kalimantan namely Kapuas. The genetic analysis was based on the sequencing of mtDNA Cytochrome b and nucleus DNA RAG2. The statistical analysis was done by using APE package on R language. The parameters observed were: nucleotide diversity, genetic distance, and neighbor-joining tree. The result showed that the highest nucleotide diversity was fish population of Musi, while the other two populations, Tulang Bawang (Sumatra) and Kapuas (Kalimantan), were considered as the lowest genetic diversity especially based on nucleus DNA RAG2 sequencing. Based on mtDNA Cytochrome-b sequencing, the most distinct population among those populations based on genetic distance were fish populations of Musi and Kapuas. According to the result of neighbor-joining tree analysis, the populations of botia were classified into two groups namely group of Sumatra and group of Kalimantan. The estimation of time divergence among group of population of Sumatra and Kalimantan based on mtDNA Cytochrome b was about 9.25—9.46 million years (Miocene era). The high genetic differences between groups of Sumatra and Kalimantan suggested that the effort of restocking botia from Sumatra into Kalimantan has to be done carefully, because it may disturb the gene originality of both botia populations.